ТҮРКІ ТІЛДЕРІНДЕГІ МОДАЛЬ СӨЗДЕР. - Молгаждаров, Қ. (Journal of Oriental Studies, 2016)
В статье рассматриваются исследования модальных слов тюркских языков и дается пояснение об историческом составе. Investigation of modal verbs of the Turkish languages is discussed in the article and explanation of historical composition is given